Role of Selective Histone Deacetylase 6 Inhibitor ACY-1215 in Cancer and Other Human Diseases - Li, Jianglei; Yu, Meihong; Fu, Shifeng; Liu, Deliang; Tan, Yuyong (Frontiers in Pharmacology, 2022)
The deacetylation process regulated by histone deacetylases (HDACs) plays an important role in human health and diseases. HDAC6 belongs to the Class IIb of HDACs family, which mainly modifies non-histone proteins located in the cytoplasm. HDAC6 plays a key role in tumors, neurological diseases, and inflammatory diseases. Therefore, targeting HDAC6 has become a promising treatment strategy in recent years. ACY-1215 is the first orally available highly selective HDAC6 inhibitor, and its efficacy and therapeutic effects are being continuously verified. This review summarizes the research progress of ACY-1215 in cancer and other human diseases, as well as the underlying mechanism, in order to guide the future clinical trials of ACY-1215 and more in-depth mechanism researches.